Analisis Kebutuhan Guru dan Peserta Didik Terhadap Model Pembelajaran Inovatif dalam Menulis Tegak Bersambung - Astuti, Vitri; Markhamah, Markhamah; Rahmawati, Laili Etika (Jayapangus Press, 2025)
The skill of handwriting, particularly in the form of cursive writing, plays a crucial role in the cognitive and motor development of elementary school students. This study aims to analyze the needs of both teachers and students in relation to innovative models for teaching cursive writing in elementary schools. The research was conducted at SDN 01 Tunggulrejo, focusing on the challenges faced by fifth-grade students who show a diverse range of abilities in cursive handwriting. The study employed a qualitative approach, using interviews, surveys, and class observations to collect data. The findings reveal that the current model of teaching cursive writing is largely conventional and ineffective in meeting the diverse needs of students. Most teachers expressed the need for more innovative, flexible, and technology-integrated models to enhance the effectiveness of handwriting instruction. Additionally, students face difficulties in maintaining consistency in letter formation and writing speed, which highlights the necessity for more interactive and engaging learning strategies. The study concludes that incorporating digital tools, educational games, and teacher training can significantly improve both the motivation and the skills of students in cursive writing. These findings suggest that an integrated approach combining conventional models with modern technologies can provide a more comprehensive and effective solution for teaching cursive handwriting in elementary education.